Optimization of control parameters of droplet density in citrus trees using UAVs and the Taguchi method - Hou, Chaojun; Tang, Yu; Luo, Shaoming; Lin, Jintian; He, Yong; Zhuang, Jiajun; Huang, Weifeng (International Journal of Agricultural and Biological Engineering, 2019)
The control parameters of the unmanned aerial vehicle (UAV) should be carefully designed to improve UAV spraying performance on citrus trees. The present study investigated the optimal droplet distribution control parameters in citrus trees using a UAV and the Taguchi method, of which optimal results were observed with an inverted triangle citrus tree canopy shape, a spraying height of 1.40 m, and a flight speed of 1.0 m/s. Among the discussed control parameters, the flight speed presented the most significant effect with a contribution percentage of 74.0%. The established multiple regression model predicted an optimal spraying height of 1.27 m and a maximum droplet density of 35.39 droplets/cm2. In addition, the effects of individual control parameter on the droplet density of the lower layer of citrus trees were systematically analyzed, of which inverted triangle shape more significantly affected the droplet density of the lower layer and presented an 82.0% increase in droplet density as compared to the triangle shape. An improvement of 59.6% in the lower layer droplet density was observed at a spraying height of 1.40 m. In addition, the other spraying heights did not present significant differences in their coefficient of variation (CV) values.Keywords: droplet density, citrus, Taguchi method, aerial spraying, unmanned aerial vehicle (UAV), plant protectionDOI: 10.25165/j.ijabe.20191204.4139Citation: Hou C J, Tang Y, Luo S M, Lin J T, He Y, Zhuang J J, et al. Optimization of control parameters of droplet density in citrus trees using UAVs and the Taguchi method. Int J Agric & Biol Eng, 2019; 12(4): 1–9.